Combining organic and mineral fertilizers for integrated soil fertility management in smallholder farming systems of Kenya : Explorations using the crop-soil model FIELD - Tittonell, Pablo A.; Corbeels, Marc; Wijk, Mark T. van; Vanlauwe, Bernard; Giller, Kenneth E. (Wiley, 2008)
Integrated soil fertility management (ISFM) technologies for African smallholders should consider (i) within-farm soil heterogeneity; (ii) long-term dynamics and variability; (iii) manure quality and availability; (iv) access to fertilizers; and (v) competing uses for crop residues. We used the model FIELD (Field-scale resource Interactions, use Efficiencies and Long term soil fertility Development) to explore allocation strategies of manure and fertilizers. Maize response to N fertilizer from 0 to 180 kg N ha?1 (±30 kg P ha?1) distinguished poorly responsive fertile (e.g., grain yields of 4.1–5.3 t ha?1 without P and of 7.5–7.5 t ha?1 with P) from responsive (1.0–4.3 t ha?1 and 2.2–6.6 t ha?1) and poorly responsive infertile fields (0.2–1.0 t ha?1 and 0.5–3.1 t ha?1). Soils receiving manure plus fertilizers for 12 yr retained 1.1 to 1.5 t C ha?1 yr?1 when 70% of the crop residue was left in the field, and 0.4 to 0.7 t C ha?1 yr?1 with 10% left. Degraded fields were not rehabilitated with manures of local quality (e.g., 23–35% C, 0.5–1.2% N, 0.1–0.3% P) applied at realistic rates (3.6 t dm ha?1 yr?1) for 12 yr without fertilizers. Mineral fertilizers are necessary to kick-start soil rehabilitation through hysteretic restoration of biomass productivity and C inputs to the soil.